MENUMBUHKAN MINAT BACA SISWA SEKOLAH DASAR MELALUI GERAKAN LITERASI SEKOLAH PADA PROGRAM KAMPUS MENGAJAR - Fifit Fitriansyah (Prima Magistra: Jurnal Ilmiah Kependidikan, 2024)
Low interest in reading among elementary school students is a sign that learning activities are not going well. Because, reading is the starting point for students to understand learning through understanding texts in reading books, for this reason, the habit of reading is something that teachers need to do continuously. The aim of this research is to foster interest in reading in elementary school students by holding a School Literacy Movement which is carried out continuously in campus teaching programs. The method used is qualitative descriptive where the presentation is based on actual observations based on empirical activities. The results of this research are that the school literacy movement carried out in the campus teaching program has fostered students' interest in reading at SDN Sarimukti 02 Bekasi through the activities MOLIQU, Literacy Tree, Literacy Corner and Information Magazine. With this activity, students become accustomed to reading and understanding the information or text they read.